2022
DOI: 10.3390/ijerph192114098
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Behavior Interventions for Preventing Cancer in Adults with Inherited Cancer Syndromes: Systematic Review

Abstract: (1) Background: The link between lifestyle behaviors and cancer risk is well established, which is important for people with personal/family history or genetic susceptibility. Genetic testing is not sufficient motivation to prompt healthier lifestyle behaviors. This systematic review aims to describe and assess interventions for promoting healthy behaviors in people at high risk of cancer. (2) Methods: The review was performed according to PRISMA guidelines using search terms related to hereditary cancer and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Regardless, the WCRF score has been associated with all-cause and site-specific cancer incidence and mortality in the general population, so behavioural interventions to increase adherence to these criteria may still have substantial benefit for those with LS. However, a systematic review of 4 randomised trials of behavioural intervention in people with genetic tumour syndromes showed mixed results [55]. One randomised trial included investigated the effect of providing WCRF health promotion materials in people with LS [56].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, the WCRF score has been associated with all-cause and site-specific cancer incidence and mortality in the general population, so behavioural interventions to increase adherence to these criteria may still have substantial benefit for those with LS. However, a systematic review of 4 randomised trials of behavioural intervention in people with genetic tumour syndromes showed mixed results [55]. One randomised trial included investigated the effect of providing WCRF health promotion materials in people with LS [56].…”
Section: Discussionmentioning
confidence: 99%